Sociology English-Urdu - (:unkn) unknown (My University, 2020)
The new series titled Translation Equivalents in Indian Languages, an initiative by NTM, will be very useful for the translators of regional languages. This will benefit the teachers, students, researchers, language enthusiasts and scholars in general and the translators, in particular.
Translation Equivalents in Indian Languages: Sociology English-Urdu
Keywords: English; Urdu